Effects of RU486 and indomethacin on meiotic maturation, formation of extracellular matrix, and progesterone production by porcine oocyte-cumulus complexes - Nagyova, E; Scsukova, S; Kalous, J; Mlynarcikova, A (Domestic animal endocrinology, 2014)
This study was designed to determine whether inhibition of either cyclooxygenase-2 (COX-2) by indomethacin or progesterone receptor (PR) by PR antagonist, RU486, affects oocyte maturation, progesterone production, and covalent binding between hyaluronan (HA) and heavy chains of inter-α trypsin inhibitor, as well as expression of cumulus expansion-associated proteins (HA-binding protein, tumor necrosis factor α-induced protein 6, pentraxin 3) in oocyte-cumulus complexes (OCCs). The experiments were based on freshly isolated porcine OCC cultures in which the consequences of PR and COX-2 inhibition on the final processes of oocyte maturation were determined. Granulosa cells (GCs) and OCCs were cultured in medium supplemented with FSH/LH (both 100 ng/mL) in the presence/absence of RU486 or indomethacin. Western blot analysis, (3)H-glucosamine hydrochloride assay, immunofluorescence, and radioimmunoassay were performed. Only treatment with RU486 (25 μM) caused a decrease in the number of oocytes that reached germinal vesicle breakdown and metaphase II stage compared with indomethacin (100 μM) or FSH/LH treatment alone after 44 h. All treated OCCs synthesized an almost equal amount of HA. Heavy chains (of inter-α trypsin inhibitor)-HA covalent complexes were formed during in vitro FSH/LH-stimulated expansion in RU486- or indomethacin-treated OCCs. Follicle-stimulating hormone/LH-induced progesterone production by OCCs was increased in the presence of RU486 after 44 h. In contrast, a decrease of FSH/LH-stimulated progesterone production by GCs was detected in the presence of either RU486 or indomethacin after 72 h. We suggest that the PR-dependent pathway may be involved in the regulation of oocyte maturation. Both PR and COX-2 regulate FSH/LH-stimulated progesterone production by OCCs and GCs.
Keywords: Animals; transportní proteiny; progesteron; Cyclooxygenase Inhibitors; Progesterone; Luteinizing Hormone; C-Reactive Protein; molekuly buněčné adheze; IVM techniky; Oocyte; Follicle Stimulating Hormone; indomethacin; Oocytes; Indomethacin; Mifepristone; oocyty; mifepriston; sérový amyloidový protein; prasata; kyselina hyaluronová; In Vitro Oocyte Maturation Techniques; extracelulární matrix; Hyaluronic Acid; RU486; regulace genové exprese; Carrier Proteins; Cumulus Cells; Swine; Hormone Antagonists; Cell Adhesion Molecules; inhibitory cyklooxygenasy; Serum Amyloid P-Component; kumulární buňky; luteinizační hormon; Extracellular Matrix; C-reaktivní protein; Granulosa; Gene Expression Regulation; zvířata; folikuly stimulující hormon; antagonisté hormonů